2007
DOI: 10.1158/0008-5472.can-07-0515
|View full text |Cite
|
Sign up to set email alerts
|

Dual Role of Mitochondrial Reactive Oxygen Species in Hypoxia Signaling: Activation of Nuclear Factor-κB via c-SRC– and Oxidant-Dependent Cell Death

Abstract: Hypoxia is a prominent feature of solid tumor development and is known to stimulate mitochondrial ROS (mROS), which, in turn, can activate hypoxia-inducible transcription factor-1A and nuclear factor-KB (NF-KB). Because NF-KB plays a central role in carcinogenesis, we examined the mechanism of mROS-mediated NF-KB activation and the fate of cancer cells during hypoxia after mitochondrial reduced glutathione (mGSH) depletion. Hypoxia generated mROS in hepatoma (HepG2, H35), neuroblastoma (SH-SY5Y), and colon car… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
153
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 202 publications
(165 citation statements)
references
References 51 publications
(80 reference statements)
10
153
0
2
Order By: Relevance
“…First, HIF-1 activates the survival pathway, acting on inhibition of proapoptotic routes such as Bad and Bid and activation of secretion of prosurvival factors such as VEGF, Bcl-2, and myeloid cell leukemia-1 [51,52]. In addition, in hepatoma cells, mitochondrial ROS due to hypoxia lead to activation of the prosurvival pathway driven by nuclear factor-κB, through oxidation/activation of the kinase Src and phosphorylation of the p65 inhibitor of nuclear factor-κB [51,53]. This is a compulsory protection system from an incremental danger, i.e., the decrease in O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…First, HIF-1 activates the survival pathway, acting on inhibition of proapoptotic routes such as Bad and Bid and activation of secretion of prosurvival factors such as VEGF, Bcl-2, and myeloid cell leukemia-1 [51,52]. In addition, in hepatoma cells, mitochondrial ROS due to hypoxia lead to activation of the prosurvival pathway driven by nuclear factor-κB, through oxidation/activation of the kinase Src and phosphorylation of the p65 inhibitor of nuclear factor-κB [51,53]. This is a compulsory protection system from an incremental danger, i.e., the decrease in O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…4), suggesting that oxidative stress is a necessary cue in ferritin H activation by rotenone. Several recent studies have reported that in some conditions, especially hypoxia, rotenone reduces mitochondrial ROS generation [34][35][36]. To date there is no clear consensus about the effect of rotenone on mitochondrial ROS generation under various conditions; however, such contradictory reports support the need for further investigation into the intricacies of mechanisms of mitochondrial ROS generation and suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Since inhibition of mitochondrial complex I by rotenone has a potential to induce production of ROS and H 2 O 2 [24], we next investigated whether ferritin H protein synthesis was transiently repressed following rotenone treatment. We exposed NIH3T3 cells to 1 uM rotenone for various times over a period of 24 hrs, and subsequently subjected them to 35 Smethionine/cysteine pulse-labeling and ferritin immunoprecipitation. As shown in Fig.…”
Section: Rotenone Induces Ferritin H Expressionmentioning
confidence: 99%
“…This then amplified, in a feed-back loop, the effect leading to further pseudo-hypoxia and HIF1a stabilization (Dahia et al, 2005;Cervera et al, 2008). Moreover, hypoxia was shown to further inhibit complex II activity and generate mitochondrial ROS (Paddenberg et al, 2003;Lluis et al, 2007). Finally, hypoxia and probably HIF1a also inhibit ATP synthase, thereby contributing to OxPhos reduction (Campanella et al, 2009).…”
mentioning
confidence: 99%